Rancang Bangun Website Desa Pulokalapa untuk Peningkatan Teknologi dan Promosi Wisata Desa - Maulana, M. Subhakti A.; Azizi, Bhanu; Sumitra, Naufal Rabbani (STIKOM Tunas Bangsa Pematangsiantar, 2026)
The development of information technology encourages villages to use digital media as a means of providing information services and promoting local potential more effectively. Pulokalapa Village has considerable potential for religious tourism and local resources, but it has not been supported by an integrated Website-based information system. This research aims to design and build the Pulokalapa Village Website as a medium for village information services as well as village tourism promotion. The research method used is system development research with a qualitative descriptive approach and Waterfall development model, which includes the stages of needs analysis, system design, coding, testing, and maintenance. The Website is developed using HTML, PHP, CSS, JavaScript, as well as MySQL Databases. The results of the study show that the Pulokalapa Village Website was successfully built according to functional and non-functional needs, and all system modules ran well based on Black Box Testing testing. This Website is able to increase the effectiveness of village information delivery, public transparency, and the promotion of tourism potential and village MSMEs. The recommendations of this study are the need for regular content updates, improving the competence of Website managers, as well as the development of online service features and user satisfaction evaluation in future research.